Relationship between serum iPTH and peritonitis episodes in patients undergoing continuous ambulatory peritoneal dialysis - Zhao, Zihao; Yan, Qianqian; Li, Duopin; Li, Guangpu; Cai, Jingjing; Pan, Shaokang; Duan, Jiayu; Liu, Dongwei; Liu, Zhangsuo (Frontiers in Endocrinology, 2023)
Background: Peritonitis is considered as one of the most serious complications caused hospitalization in patients undergoing continuous ambulatory peritoneal dialysis. There was limited evidence on the impact of PTH on the first peritoneal dialysis-associated peritonitis episode. We aimed to investigate the influence of serum iPTH on peritonitis in peritoneal dialysis patients. Methods: This was a retrospective cohort study. The initial continuous ambulatory peritoneal dialysis patients from a single center in China were enrolled. Baseline characteristics and clinical information were recorded. The primary outcome of interest was the occurrence of the first PD-associated peritonitis episode. Five Cox proportional hazard models were conducted in each group-set. In group-set one, all participants were divided into three subgroups by tertiles of serum concentration of iPTH; in group-set two, all participants were divided into three subgroups by serum concentration of iPTH with 150 pg/mL interval (< 150 pg/mL, 150-300 pg/mL, > 300 pg/mL). Hazard ratios and 95% confidence interval was calculated in each model. Multivariate linear regression analysis elimination procedure assessed association between clinical characteristics at baseline and iPTH. Restricted cubic spline models and stratiﬁed analyses were also conducted. Results: A total of 582 initial peritoneal dialysis patients (40 % female; mean age 45.1±11.5 years) from a single center in China were recruited and the median follow-up period was 25.3 months. Multivariate Cox regression analysis showed that, in the fully adjusted model, higher serum iPTH level (tertile 3, and iPTH >300 pg/mL) was significantly associated with higher peritoneal dialysis-associated peritonitis at 3- year risk (tertile 3: hazard ratio, 1.53, 95% confidence interval, 1.03 to 2.55, p= 0.03; iPTH >300 pg/mL: hazard ratio, 1.57, 95% confidence interval, 1.08 to 2.27, p= 0.02). The hazard ratio for every 100 pg/mL increase in serum iPTH level was 1.12 (95% confidence interval, 1.05 - 1.20; p <0.01) in total cohort when treated iPTH as a continuous variable. Conclusions: An elevated iPTH level was significantly associated with an increased risk of peritonitis in patients undergoing continuous ambulatory peritoneal dialysis.